2016
DOI: 10.1002/elan.201600262
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Surface Characterization of Dense Monolayers Grafted on ITO and Si/SiO2 Surfaces via Tetra(tert‐Butoxy)Tin Linker

Abstract: Indium tin oxide (ITO) and silicon with a thermally grown SiO2 layer (Si/SiO2) substrates have been functionalized by ferrocene bound through Sn(O)x (x=2 or 3) linkers preliminarly grafted on the surface by reaction of the terminal hydroxyl groups with tetra(tert‐butoxy)tin. The two steps modification of the surface was carried out by chemical vapour deposition metathesis reaction producing a self‐assembled monolayer of ferrocene. The ITO and Si/SiO2 thus functionalized have been characterized by voltammetric,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Samples for the AFM experiments were prepared by depositing the oligomeric film through electrochemical polymerization, of either a ACN or DCM monomer solution, on ultra-flat ITO (uflat-ITO), with a sheet resistance of 7 Ω sq –1 , RMS roughness of about 0.6 nm (1 × 1 μm 2 ), provided by Kuramoto Co. (Kurihara, Japan). The images were obtained by optimizing the setpoint tapping amplitude with respect to the free amplitude of the probe, near the resonance frequency of the probe itself, as reported elsewhere 47. The thickness of the deposit was evaluated by scratching an area of the deposit with the AFM tip by applying a minimum constant force (130 nN) in contact mode and subsequently performing the imaging of the selected surface part in tapping mode.…”
Section: Methodsmentioning
confidence: 99%
“…Samples for the AFM experiments were prepared by depositing the oligomeric film through electrochemical polymerization, of either a ACN or DCM monomer solution, on ultra-flat ITO (uflat-ITO), with a sheet resistance of 7 Ω sq –1 , RMS roughness of about 0.6 nm (1 × 1 μm 2 ), provided by Kuramoto Co. (Kurihara, Japan). The images were obtained by optimizing the setpoint tapping amplitude with respect to the free amplitude of the probe, near the resonance frequency of the probe itself, as reported elsewhere 47. The thickness of the deposit was evaluated by scratching an area of the deposit with the AFM tip by applying a minimum constant force (130 nN) in contact mode and subsequently performing the imaging of the selected surface part in tapping mode.…”
Section: Methodsmentioning
confidence: 99%
“…The TEM image showed that the prepared AuNPs were nearly monodisperse spheres with an average size of about 14 nm (Figure S1-B) and an average hydrodynamic diameter of ∼21 nm (Figure S1-C). However, the absorption peak of AbFc@AuNPs appeared at 528 nm (Figure S1-A, curve b), which most likely resulted from a change in the dielectric property of the media surrounding the AuNPs, , demonstrating the successful comodification of Fc and antibody on the AuNP surface.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Petrizza et al . developed a self‐assembled monolayer of ferrocene‐based on two steps modification of the surface . It was carried out with the help of vapor deposition metathesis reaction.…”
Section: Ferrocene‐based Electro Responsive Materialsmentioning
confidence: 99%
“…The resultant product carried a homogeneous robust and densely packed electro responsive monolayer. This system can be used to explore in the area of sensing and optoelectronic devices (Figure ) …”
Section: Ferrocene‐based Electro Responsive Materialsmentioning
confidence: 99%
See 1 more Smart Citation